정유산업의 암모니아 배출계수 산정 - 김고은(Kim, Go Eun); 강성민(Kang, Sung Min); 노준영(Roh, Jun Young); 공부주(Kong, Boo-Joo); 김기홍(Kim, Gi Hong); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2022)
Nitrogen oxide (NOx), sulfur oxide (SOx), volatile organic compounds (VOCs), and ammonia (NH3) are some of the precursors that contribute to the secondary generation of particulate matter less than 2.5 ㎛ in diameter (PM-2.5). Among them, ammonia is relatively poorly managed and researched, although it contributes to secondary generation of PM-2.5 and requires integrated management as a short-lived climate pollutant (SLCP). In the 2017 National Air Pollutant Emission Statistics of the National Fine Dust Information Center, NH3 emissions in the oil refining industry accounted for 58% of the total production process emissions, but for the calculation of NH3 emission, the USA AP-42 (1994) emission factors is used. In this study, an NH3 emission factor was developed, and related characteristics were analyzed through on-site visits to oil refineries and measurement of ammonia emissions. The measurements showed an ammonia emission factor of the oil refining industry of 0.002 kgNH3/kL, which was much lower than the existing AP-42 emission factor of 0.155 kgNH3/kL. This indicates that the current emission factor guideline needs to be improved. Using the newly proposed emission factor, NH3 was calculated at 32 tons/yr, a difference of 24,920 tons/yr based on the current NH3 emission of 24,953 tons/yr shown in the national air pollutant emission statistics. KCI Citation Count: 0